2014
DOI: 10.1002/jbm.a.35086
|View full text |Cite
|
Sign up to set email alerts
|

Structural and antigenic stability of H5N1 hemagglutinin trimer upon release from polyanhydride nanoparticles

Abstract: Although H5N1 avian influenza has not yet acquired the capacity to readily infect humans, should it do so, this viral pathogen would present an increasing threat to the immunologically naïve human population. Subunit vaccines based on the viral glycoprotein hemagglutinin (HA) can provide protective immunity against influenza. Polyanhydride nanoparticles have been shown to enhance efficacy of subunit vaccines, providing the dual advantages of adjuvanticity and sustained delivery resulting in enhanced protein st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
68
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 51 publications
(78 citation statements)
references
References 32 publications
10
68
0
Order By: Relevance
“…18,19 Previously, soluble H5 HA trimers (sH5 3 ) from H5N1 influenza virus A/Whooper Swan/Mongolia/244/05 were produced using a baculovirus insect cell expression system and shown to maintain their oligomeric structure and antigenicity upon release from polyanhydride nanoparticles. 20 In this study, the immunogenicity and virus-neutralizing antibody titer in response to nanovaccine immunization were observed for approximately 2 months, and concluded with an analysis of memory T cell responses. Finally, the efficacy of the nanovaccine formulations was examined using a lowpathogenic, live-viral challenge.…”
Section: Ross Et Almentioning
confidence: 60%
See 1 more Smart Citation
“…18,19 Previously, soluble H5 HA trimers (sH5 3 ) from H5N1 influenza virus A/Whooper Swan/Mongolia/244/05 were produced using a baculovirus insect cell expression system and shown to maintain their oligomeric structure and antigenicity upon release from polyanhydride nanoparticles. 20 In this study, the immunogenicity and virus-neutralizing antibody titer in response to nanovaccine immunization were observed for approximately 2 months, and concluded with an analysis of memory T cell responses. Finally, the efficacy of the nanovaccine formulations was examined using a lowpathogenic, live-viral challenge.…”
Section: Ross Et Almentioning
confidence: 60%
“…By encapsulating H5 antigen into polyanhydride nanoparticles, the foundation has been laid for the design of pandemic influenza vaccines with improved efficacy by demonstrating reduced variability in the neutralizing antibody titer, enhanced T cell responses, and greater stability. 20 As mentioned above, the recent seasonal influenza vaccine is approximately 60% effective; however, this estimate has a 95% confidence interval of 5%-68%, 35 which is a substantial range that indicates the large (and unacceptable) variability of the host responses to the vaccine. Variability of vaccine effectiveness can be influenced by a large number of factors, including age, obesity, nutrition, or other disease(s) present in the host.…”
Section: Discussionmentioning
confidence: 98%
“…231 Finally, a recent study demonstrated the structural and antigenic stability of HA encapsulated into polyanhydride nanoparticles. 232 When designing HA-based vaccines, preserving antigen stability is essential to enable recognition of conformational epitopes that may lead to enhanced production of neutralizing antibody titers and cross-protection. The release of stable HA immunogen after encapsulation into polyanhydride nanoparticles ultimately led to robust, cross-clade neutralizing antibody responses postimmunization that protected mice from a live viral challenge.…”
Section: Polymer Chemistrymentioning
confidence: 99%
“…Biodegradable polyanhydride particles have high biocompatibility, controllable degradation rates due to their surface erosion degradation mechanism, and a favorable microenvironment resulting from their less acidic degradation products (Determan et al, 2004;Kipper et al, 2002Kipper et al, , 2006Lopac et al, 2009;Torres et al, 2007;Torres et al, 2011;Ulery et al, 2011a). Specifically, polyanhydride micro-and nanoparticles have been successfully used for sustained delivery and stabilization of several protein-based vaccines (Carrillo-Conde et al, 2010;Determan et al, 2006a;Haughney et al, 2013;Petersen et al, 2012;Ross et al, 2014;Torres et al, 2007;Ulery et al, 2011aUlery et al, , 2011b.…”
Section: Introductionmentioning
confidence: 98%